A Magnetically Recyclable Fe₃O₄/GO/Chitosan Nanocomposite for Water Decontamination and Electrocatalytic Hydrogen Evolution - Ismail, M. Mohamed; Sankar, A. (International Journal of Aquatic Research and Environmental Studies, 2026)
Water pollution caused by industrial waste, dyes, and heavy metals has become a major environmental concern worldwide. In this study, a nanocomposite material was synthesized and characterized for its potential application in water purification and clean energy generation. The nanocomposite was prepared using a simple chemical synthesis method to combine the advantageous properties of iron oxide nanoparticles, graphene oxide, and chitosan. The synthesized material was characterized using various analytical techniques such as UV–Visible spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) to determine its structural, optical, and surface properties. The characterization results confirmed the successful formation of the nanocomposite with good surface morphology, magnetic responsiveness, and stability. The prepared nanocomposite was evaluated for the removal of pollutants from contaminated water through adsorption and catalytic activity, and separately for its electrocatalytic performance toward the hydrogen evolution reaction (HER). Experimental results indicated that the material showed effective purification performance with improved removal efficiency and reusability, achieving maximum adsorption capacities of 204.1 mg/g for methylene blue and 142.9 mg/g for Pb²⁺ ions. Furthermore, the nanocomposite exhibited an overpotential of 320 mV at 10 mA/cm² for HER with a Tafel slope of 98 mV/dec and stable operation for 10 hours. The study demonstrates that this nanocomposite material can serve as a promising and environmentally friendly candidate for advanced water treatment applications and as a low-cost electrocatalyst for hydrogen production.